Nursing care facing the recognition of patients' belief or religion: undergraduates' perceptions - Janei Rabello Souza; Dulce Huf Bais; Mariluci Alves Maftum (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Descriptive-exploratory research carried out in 2006 with 10 nursing undergraduates from the tenth term. Data were collected by means of a semi-structured interview and results were organized in 5 theme-categories: Featuring subjects. The importance for human beings to believe in a superior entity. The nurse as a facilitator for patients to bond whatever may provide them strength to face suffering. Knowing and respecting patients' belief / religion for effective nursing care. Students' understanding of human beings' spiritual dimension. It was evidenced that students value all forms of people's spiritual expression and were concerned to deliver nursing care in human beings' spiritual dimension, even those who stated not to have a specific belief or religion, acknowledged the significance of such care. They pointed out the importance of believing in a superior entity for human beings and man usually believes in something, in a god. They considered indispensable for nurses to help those who believe in something that make their lives meaningful, to connect with such a force in order to face and overcome crises, disease and even death. They pondered that an effective care deems necessary for caregivers to use empathy and by means of actions such as listening and talking, nurses may foster comfort and help for patients and their families, which is a significant expression of nursing care.